Dampak Identifikasi Penyebab Rendahnya Pelaporan Insiden Keselamatan Pasien di Rumah Sakit Umum Daerah Panembahan Senopati Bantul: Sebuah Studi Kasus - Sely Aprianda Syah Putri; Betha Candra Sari; Adi Utarini (The Journal of Hospital Accreditation, 2023)
Background: Patient safety is a serious problem that occurs globally, which affects the quality of health services. Reporting patient safety incidents is at the heart of service quality, but those who carry it out are still lacking, health workers' awareness of this is still quite low. Based on initial observations, as of June 2022 there were 24 reports. This condition is far below the IOM estimate which states that the IKP rate is around ± 10% of the number of hospitalized patients. One of the efforts to improve the quality of IKP is the contribution of the District Health Authority in monitoring and evaluation. Objective: Identifying the causes of low reporting of patient safety incidents at RSUD Panembahan Senopati. Methods: This type of research is a case study conducted by in-depth interviews and document review. The subjects of this study consisted of the chairman of the Hospital Patient Safety Sub-Committee, the secretary of the Hospital Patient Safety Sub-Committee, the coordinator and officers in the emergency room unit, nakula sadewa pediatric room, arjuna bisma room, setyaki surgical room and the District Health Authority Bantul. The sampling method in this study used purposive sampling technique with technical analysis using pattern matching. Results: RSUD Panembahan Senopati is trying to establish a learning culture dimension in building a patient safety culture. The inhibiting factors in IKP reporting at this hospital are individual understanding, fear of blame, reporting process, organization/system and work environment. Meanwhile, the supporting factors are interpersonal relationships, motivation and rewards. The District Health Authority Bantul has not optimized its role in carrying out guidance and supervision according to the Indonesian Ministry of Health Circular Letter Number HK.02.02/I/4254/2021. Conclusion: The low reporting of patient safety incidents at Panembahan Senopati Hospital is caused by several factors, namely the lack of individual understanding, the fear of being blamed, the reporting process, the organization and the hospital work environment, even though this hospital has an internal policy in the form of Director Regulation Number 12 of 2022 and formed a PIC / Champion as an effort to cultivate IKP reporting. Keywords: Patient safety incident reporting, Patient Safety, Berwick's Theory, The role of District Health Authorities